Motivation for Physical Activity as a Key Determinant of Sedentary Behavior Among Postsecondary Students - Rachel Surprenant MEd; Isabelle Cabot PhD; Caroline Fitzpatrick PhD (SAGE Publishing, 2024)
It is known that the transition to adulthood represents a critical period of life when acquiring healthy behaviors can influence lifestyle and health throughout adulthood. Given the importance of the consequences of a sedentary lifestyle, identifying influence factors is key to improving healthy behaviors. The objective of this study is to explore the role of postsecondary students' motivation toward physical activity in the association with their screen time and out-of-school physical activity practice. A total of 1522 postsecondary students (90% were aged 17-20 years) recruited from 17 postsecondary institutions completed the self-reported questionnaire during course time. Multivariate linear regression was used to assess the association between motivation to move including additional predictors of behavior such as intention and tendency to self-activate and self-reported screen time and physical activity controlling for age and sex. Motivation including all 3 motivational variables (interest, utility, competence) was negatively associated with screen time, b  = −0.498 (95% CI between −0.635 and −0.361) and positively associated with moderate-to-vigorous physical activity, b  = 133.986, (95% CI between 102.129 and 165.843). Of the 3 motivational variables, interest had the strongest negative association with screen time, b  = −0.434 (95% CI between −0.551 and −0.317), and the strongest positive association with physical activity, b  = 113.671, (95% CI between 86.396 and 140.946). These findings indicate that the motivation of postsecondary students toward physical activity significantly influences their behaviors, including screen time and physical activity engagement.